LOAD-BEARING PRECAST FOAMED CONCRETE SANDWICH WALL - Noridah Mohamad; Abdul Aziz Abdul Samad; Jayaprakash Jaganathan (Penerbit UTHM, 2018)
This book presents the structural behavior, advantages, and application of precast lightweight foamed concrete sandwich panel (PLFP) as a load-bearing wall. PLFP is fabricated from lightweight materials as its inner and outer layers. It has higher strength to weight ratio compared to conventional concrete. The overall strength is sufficient due to the efficiency of the steel shear truss connector that is able to hold the various layers in it. This wall is feasible to be developed as a load-bearing wall in low to medium rise building. The content of this book is suitable as a reference for undergraduate and postgraduate student in Structural Engineering. It provides the fundamental knowledge on the structural behavior of precast wall under buckling and how its materials and connectors influence its overall behavior. The structural behavior is presented in the context of its ultimate load, crack pattern, failure mode, load-deflection profile, and strain distribution. This book is also suitable as guidance to construction industry players and local contractors who have limited knowledge on strength capacity and advantages of precast lightweight sandwich wall. The comprehensive content of the book could benefit the contractors because it provides the information on the materials used, fabrication, test-set-up, and analysis of the results obtained from the tests. It also explains in details on the advantages of using this system compared to conventional wall, which include its speed of construction, neater site, and less number of laborers required. It is hoped that this book could encourage more local contractors to implement precast IBS system in building construction, thus meet the demand for affordable and quality housing.